Evaluasi Pelatihan Jarak Jauh Business English I Pada Balai Pendidikan Dan Pelatihan Keuangan Denpasar - Dyah Indrawati, Efi; Lestyowati, Jamila (CV. Multi Kreasi Media, 2024)
Distance Training (PJJ) of Business English I is intended to improve the competence of Ministry of Finance employees to use English in carrying out organizational tasks and functions, especially in conducting business conversations and practicing basic business writing. This study aims to evaluate the effectiveness of PJJ Business English using the Kirkpatrick Evaluation Model Level 1 (Reaction) and Level 2 (Learning). The evaluation is used to obtain the participants’ satisfaction and their skills improvement in English. The research method used is a mixed method. Quantitative data were obtained through participant satisfaction surveys at the Reaction level and pre-post-test results at the Learning level. Qualitative data were collected through in-depth interviews to explore participants' experiences and perceptions of the training. The results showed that participants were satisfied with the training with an average high level of satisfaction. At the Learning level, there was a significant increase in participants' business English skills, such as understanding business terms and written communication skills. These findings indicate that distance training of Business English I is effective in improving participant competence. The implications of the results of this study can be a reference in the development of more structured distance training on business English that is tailored to the needs of participants.